Introduction of Performance Budgeting in Telephones (Communications) - Planning Commission, Government of India (Planning Commission, Government of India, 1966)
The document outlines the telecommunications development plans in India during the Third Plan period, focusing on the expansion of telephone services, including the installation of telephones, private branch exchanges, and automatic exchanges. It details the progress made in establishing Public Call Offices (P.C.Os) in rural areas, the installation of coaxial cables, and the financial allocations for various telecommunications projects. The report highlights the challenges faced in achieving the targets set for the expansion of telecommunication infrastructure and provides a breakdown of expenditures related to different schemes and operational costs.
Development Administration Unit Management and Administration Division Committee on Plan Projects
Committee on Plan Projects Planning Commission
Keywords: Telecommunications Development; Third Plan; Public Call Offices; Automatic Exchanges; Coaxial Cables; Telephone Services; Rural Connectivity; Financial Allocations; Infrastructure Expansion; Private Branch Exchanges